Low temperature synthesis of nanocrystalline lithium ferrite by a modified citrate gel precursor method - Verma, Seema; Joy, Pattayil Alias (Materials Research Bulletin, 2008)
Single phase nanocrystalline lithium ferrite is synthesized by a modified citrate gel precursor technique. Ferrite nanoparticles of average size of 8 nm, obtained after calcination of the citrate gel Made by the usual method at 450 degrees C, show superparamagnetic behavior. However, small amounts of alpha-Fe(2)O(3) is formed as an impurity phase clue to the initial formation of some gamma-Fe(2)O(3) phase. Oil the other hand, when the pH of the mixed Solution is increased to 7 after the addition of ammonia Solution, a lower calcination temperature of 200 degrees C is sufficient for the formation of single phase lithium ferrite nanoparticles of size 30 nm. No impurity phases are detected when the nanocrystalline powders arc calcined at higher temperatures. The magnetic properties of the ferrite nanoparticles of different sizes obtained by calcining the powders at different temperatures are studied. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Magnetic materials; magnetic properties; Nanostructures; Oxides

On the structural, magnetic and electrical properties of sol-gel derived nanosized cobalt ferrite - Gopalan, E. Veena; Joy, Pattayil Alias; Al-Omari, I. A.; Kumar, D. Sakthi; Yoshida, Yasuhiko; Anantharaman, Maliemadom R. (Journal of Alloys and Compounds, 2009)
Nanoparticles of cobalt ferrite were synthesized by sol gel method. These particles were structurally characterized by using X-Ray Diffraction and Transmission Electron Microscopy, High Resolution Transmission Electron Microscopy, Energy Dispersive Spectrum and Inductively Coupled Plasma Analysis and the results confirmed the formation of spherically shaped nanoparticles of cobalt ferrite having a size lying in the range of 13-14 nm. The as prepared sample was sintered at 800 degrees C and the structural, magnetic and dielectric properties were measured. The dielectric properties were studied and analyzed as a function of temperature and frequency. The ac and dc conductivity studies were carried out to delve into the conduction mechanism. The existing models based on quantum mechanical tunneling were effectively employed to explain the frequency dependent conductivity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Electronic Transport; Magnetic measurements; Magnetically ordered materials; Nanostructures; Scanning and transmission electron microscopy; Sol-gel synthesis; X-ray diffraction